Indonesia : Technical Assistance Report. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2018)
Technical Assistance Report - Residential Property Price Statistics Capacity Development Mission.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet